Association Between Internet Gaming Disorder And Attention Deficit Hyperactivity Disorder: A Narrative Review - Bumozah, Hanin; Alabdulbaqi, Donna (Journal of Community Medicine and Health Solutions, 2022)
Background: The rapid increase in the popularity of internet use and video games is associated with multiple consequences and comorbidities; therefore, investigating this issue is important, especially now that the number of people playing video games has reached approximately 2.2 billion people worldwide. Method: This paper reviews the existing literature on Google Scholar and PubMed to examine the association between internet gaming disorder (IGD) and attention deficit hyperactivity disorder (ADHD) between 2013 and 2020. Result: The reviewed studies reveal a statistically significant association between ADHD and IGD. The reviewed studies demonstrate that ADHD is a predictive factor for the development and persistence of IGD and affects the severity of IGD symptoms. Conclusion: Especially among those with ADHD, IGD causes life distress and social life impairment. This review indicates a statistically significant association between ADHD and IGD; however, longitudinal studies are needed to assist the direction of this association and make relevant and appropriate recommendations to prevent its consequences and comorbidities.